Theoretical and practical aspects of construction and security of the Ukrainian segment of the tree of identifiers of the state information resources - Бучик, C. C.; Юдін, О. К. (Science-based technologies, 2017)
In the articles expounded theoretical and practical aspects of construction and security of the Ukrainian segment of tree of identifiers of state informative resources are with reference to own authorial original developments in the cut of certain general conception of the conducted researches. Contradiction is certain between present state informative resources and normatively-legal, organizational and technical directions of their security, and as a result, presence of the imperfect system of operative management and security of informative resources of the state on the basis of organization of the system of minimization of risks of state informative resources and forming of dynamic complex of functional types of security. From present contradiction the scientifically-applied problem is shown: increase of efficiency of the system of operative management and security of informative resources of the state on the basis of organization of the system of minimization of risks to the state informative resources and forming of dynamic complex of functional types of security. The generalized is got scientific results are a practical base for a construction and security of the Ukrainian segment of knots of the information-telecommunication system of tree of identifiers of state informative resources.